The Vowel Structure of Proto-Makassar: A Phonological Reconstruction of Five Dialects - Kaharuddin; Rahman, Fathu; Abbas, Asriani; Hasjim, Munira; Muliadi (Journal of language teaching and research, 2025)
The main objective of this study is to show the reconstruction of vowels in five dialects of the Makassar language (BMP) to determine its proto-vowels. The five Makassar dialects studied are Lakiung (LK), Turatea (TRT), Bantaeng (BTG), Konjo (KJ), and Selayar (SLY). The reconstruction of the proto-phonemes of the Makassar language (BMP) was carried out using qualitative comparative methods. To facilitate the discussion, the reconstruction criteria were carried out systematically and in an orderly manner, which involved compiling corresponding words that potentially exist among the related dialects, identifying cognate words, establishing sound correspondence sets, and determining proto-phonemes. Based on the comparison and reconstruction conducted on the five Makassar dialects, it was found that BMP has five vowel phonemes. These five vowel phonemes are /*a, *o, *e, *i, and *u/. As for diphthong phonemes, none were found in any of the five Makassar dialects. Only sequential vowels were present. The phonetic data show that the intonation structure in the five Makassar dialects does not indicate the presence of two consecutive vowels (paired vowels) pronounced simultaneously or with a single breath. All double vowels in the five Makassar dialects are clearly pronounced, followed by a pause or a glide sound /w/ or /j/. This indicates that diphthong vowels do not exist in BMP.